Regulation of N6-Methyladenosine in the Differentiation of Cancer Stem Cells and Their Fate - Xu, Ya; Liu, Jing; Chen, Wen-Jia; Ye, Qian-Qian; Chen, Wen-Tian; Li, Chun-Lan; Wu, Hua-Tao (Frontiers in Cell and Developmental Biology, 2020)
N6-methyladenosine (m6A) is one of the most common internal RNA modifications in eukaryotes. It is a dynamic and reversible process that requires an orchestrated participation of methyltransferase, demethylase, and methylated binding protein. m6A modification can affect RNA degradation, translation, and microRNA processing. m6A plays an important role in the regulation of various processes in living organisms. In addition to being involved in normal physiological processes such as sperm development, immunity, fat differentiation, cell development, and differentiation, it is also involved in tumor progression and stem cell differentiation. Curiously enough, cancer stem cells, a rare group of cells present in malignant tumors, retain the characteristics of stem cells and play an important role in the survival, proliferation, metastasis, and recurrence of cancers. Recently, studies demonstrated that m6A participates in the self-renewal and pluripotent regulation of these stem cells. However, considering that multiple targets of m6A are involved in different physiological processes, the exact role of m6A in cancer progression remains controversial. This article focuses on the mechanism of m6A and its effects on the differentiation of cancer stem cells, to provide a basis for elucidating the tumorigenesis mechanisms and exploring new potential therapeutic approaches.